2016
DOI: 10.5603/gp.2016.0069
|View full text |Cite
|
Sign up to set email alerts
|

Evolution in the approach to overlooked ureteral injuries after gynecological surgery

Abstract: Objectives: To analyzed the therapeutic results for patients with overlooked iatrogenic ureteral injuries after gynecological surgery, treated at the department since 1990. Before the era of endourology, ureteral injuries were operated on immediately after making a diagnosis. This approach was changed after the popularization of percutaneous nephrostomy (PN) and ureteral stenting using a JJ stent. Material and methods:27 patients who were diagnosed with a ureteral injury between the first and sixty-fourth day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Renal cell carcinoma (RCC) accounts for about 4% of all adult malignancies. RCC occurs in both sporadic and heritable forms ( 1 ). Genetic mutations have been identified as the cause of inherited cancer in 1–2% of RCC.…”
Section: Introductionmentioning
confidence: 99%
“…Renal cell carcinoma (RCC) accounts for about 4% of all adult malignancies. RCC occurs in both sporadic and heritable forms ( 1 ). Genetic mutations have been identified as the cause of inherited cancer in 1–2% of RCC.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, further management, primarily ureteral stent placement, is mandatory for complete resolution. Borkowski et al 9 reported a complete recovery of 28.6% (6/21) with percutaneous nephrostomy alone, while this rate was 83% (5/6) for the ureteral stent group. Similarly, our complete resolution rate with percutaneous nephrostomy alone was relatively low (n = 4/12, 30%), while it was 68% (n = 19/28) for ureteral stent.…”
Section: Discussionmentioning
confidence: 99%
“…8 Urinary diversion by percutaneous nephrostomy may serve as a bridging therapy prior to surgery or can be the definitive treatment. Although Lask et al 7 reported a complete recovery rate of 80% with percutaneous nephrostomy, Borkowski et al 9 reported a recovery rate of 28.6% in patients treated with percutaneous nephrostomy alone. Therefore, ureteral stent placement should be performed following nephrostomy to preserve ureteral integrity.…”
mentioning
confidence: 99%
“…Regarding the specific treatment for postoperative ureteral obstruction, recent literature predominantly favors methods using a ureteroscopic retrograde or percutaneous nephrostomy antegrade stent. [25][26][27] Although this procedure is often successful in the case of ureteral kinking, overcoming a real obstruction with splinting of the ureter does not always succeed. In these circumstances it will be necessary to switch to an alternative direct renal urinary drain using a nephrostomy catheter, may be for longer time.…”
Section: The Significance Of An Early Therapeutic Intervention In Ure...mentioning
confidence: 99%